Arquitectura al servicio de la devoción: las capillas del Santo Cristo y Nuestra Señora de la Soledad en la colegiata de Alcañiz (Teruel). 1579-1580 y 1698-1732: Architecture at the service of devotion: the chapels of Holy Christ and Virgin of Solitude in the collegiate church of Alcañiz (Teruel). 1579-1580 and 1698-1732 - Martín Marco, Jorge (Artigrama, 2020)
Resumen La llegada de las imágenes de un Cristo Crucificado y la Virgen de la Soledad a la colegial de Alcañiz (Teruel) en 1572 fue uno de los primeros casos de la presencia de esta devoción y del empleo del modelo ideado por Gaspar Becerra para el convento de mínimos de Madrid en Aragón. Para albergar las imágenes se construyó la primera capilla entre 1579 y 1580 que fue sustituida por la actual, trazada por Gaspar Serrano y materializada entre 1698 y 1732, ambas, edificadas en dos contextos arquitectónicos diferentes uno de otro. Abstract The arrival of the images of a Crucified Christ and the Virgin of Solitude to the college of Alcañiz (Teruel) in 1578 was one of the first cases of the presence of this devotion and the use of the model devised by Gaspar Becerra for the convent of minimum of Madrid in the Aragonese kingdom. To house the works, the first chapel was built between 1579 and 1580 which was replaced by the current one, designed by Gaspar Serrano and materialized between 1698 and 1732, both built in two very different architectural contexts. Keywords Late-gothic architecture, Virgin of Solitude, Baroque architecture, Gaspar Serrano, Collegiate church of Alcañiz